Comprehensive assessment of equipment maintainability testability and supportability. Issue 1 (1st December 2022) - Quan, Li; Liu, Baoding; Liu, Haigang; Yu, Jinsong; Li, Xin
Abstract: General quality characteristics can reflect the performance and quality of equipment and have great guiding significance for the design, production, trade, and use of equipment. Maintainability, testability, and supportability (MTS) are all related to equipment faults and maintenance support and have strong relevance between them. Solving the problem of the isolation of the three characteristics evaluation requires to reduce the duplication of work and improve the evaluation efficiency, comprehensively assessment methods based on model and test are proposed by analysing the correlation of the MTS parameters. In the case study, parameters of different characteristics are obtained instead of one single characteristic, which shows the effectiveness of the proposed methods compared with the traditional sequential assessment method.